IMMU-01. MYELOID-DERIVED SUPPRESSOR CELL HETEROGENEITY DRIVES GLIOBLASTOMA PROGRESSION IN A SEX-DEPENDENT MANNER. (11th November 2019) - Bayik, Defne; Silver, Daniel; Park, Chihyun; Watson, Dionysios; Sorensen, Mia; Roversi, Gustavo; Lauko, Adam; Alban, Tyler; Lo, Alice; Sims, Peter; Barnholtz-Sloan, Jill; Kristensen, Bjarne; et al.
Abstract: An immunosuppressive tumor microenvironment is a major factor facilitating glioblastoma (GBM) progression and therapeutic resistance. Immunotherapies have had variable success in improving the outcome of GBM patients, suggesting that there is a need to gain insight into the mechanisms of immunosuppression. Our group previously demonstrated that myeloid-derived suppressor cells (MDSCs) expand in GBM patients and infiltrate tumors, where they suppress the activity of cytotoxic cells. However, the mechanisms by which individual MDSC subsets promote tumorigenesis remain understudied. Using the syngeneic mouse glioma models GL261, CT-2A and SB28, we show that monocytic MDSCs (mMDSCs) are prevalent in tumors and that their frequency is significantly higher in males, who constitute 60% of GBM patients and have a worse prognosis than females. mMDSC abundance was further associated with poor survival, and male mice reached morbidity endpoint earlier. Consistent with preclinical observations, male GBM patient specimens had significantly more IBA+CD204+ immunosuppressive myeloid cells compared to female GBM tissue. In contrast, female tumor-bearing mice had a two-fold increase in circulating granulocytic MDSC (gMDSC) frequency, while this population remained unchanged in males. Female-to-male bone marrow chimeras demonstrated that intrinsic discrepancies in immune cell characteristics drive the sex differences in survival. Consistent with the differential MDSC accumulation pattern, targeting gMDSCs with anti-Ly6G neutralizing antibodies extended the lifespan of female mice without providing a survival advantage to males. However, mMDSCs were protected from the anti-Ly6C depletion strategy due to their systemic and local proliferation, as indicated by ex vivo Ki-67 staining and subsequently confirmed by gene expression analysis. Drug-prediction algorithms using the differential RNA sequencing profiles demonstrated that mMDSCs can be targeted by chemotherapeutics, while immunomodulatory drugs are effective against gMDSCs. Collectively, these findings indicate that MDSC subset variation might represent a therapeutic opportunity for improved therapeutic efficacy of immunotherapies while accounting for sex as a biological variable.